Germinal center hypoxia in tumor-draining lymph nodes negatively regulates tumor-induced humoral immune responses in mouse models of breast cancer. (1st January 2021) - Firmino, Natalie S; Cederberg, Rachel A; Lee, Che-Min; Shi, Rocky; Wadsworth, Brennan J; Franks, S Elizabeth; Thomas, Kiersten N; Decotret, Lisa R; Bennewith, Kevin L
ABSTRACT: Hypoxia develops in germinal centers (GCs) induced by model antigens; however, it is unknown whether tumor-reactive GCs are also hypoxic. We identified GC hypoxia in lymph nodes (LNs) draining murine mammary tumors and lethally irradiated tumor cells, and found that hypoxia is associated with the levels of antibody-secreting B cells. Hypoxic culture conditions impaired the proliferation of activated B cells, and inhibited class-switching to IgG1 and IgA immunoglobulin isotypes in vitro . To assess the role of the hypoxic response in tumor-reactive GCs in vivo, we deleted von Hippel-Lindau factor (VHL) in class-switched B cells and found decreased GC B cells in tumor-draining LNs, reduced class-switched and tumor-specific antibodies in the circulation, and modified phenotypes of tumor-infiltrating T cells and macrophages. We also detected the hypoxia marker carbonic anhydrase IX in the GCs of LNs from breast cancer patients, providing evidence that GC hypoxia develops in humans. We conclude that GC hypoxia develops in TDLNs, and that the hypoxic response negatively regulates tumor-induced humoral immune responses in preclinical models.